Adversity Resilience and Self-Regulation on Students' Mathematical Competence in Elementary Schools - Wiguna, I Nyoman Artha; I Made Candiasa; Ida Bagus Putu Arnyana (Universitas Pendidikan Ganesha, 2024)
There are various problems among students when learning mathematics. One of the main problems is that individuals have different views regarding the difficulty of mathematics subjects. This research aims to analyze the resilience and self-regulation of students' mathematical competence. This type of research is causal survey research with SEM (Structural Equation Modeling) analysis techniques. The research sample consisted of 153 students, determined using the Slovin formula and selected randomly. Resilience and self-regulation data were collected through questionnaires, while mathematics competency data were collected through tests. Data were analyzed using SEM analysis. The findings show that resilience and self-regulation influence mathematical competence. Resilience has a positive effect on students' mathematical competence. Self-regulation has a positive impact on students' mathematical competence. Resilience has a positive effect on students' self-regulation. This research concludes that resilience and self-regulation influence students' mathematical competence. The research implications can contribute to mathematics learning, namely the importance of increasing mathematical competence through growing mastery for appropriate actions, which will impact achieving more optimal mathematical competence in students.